A Microbial Fermentation Mixture Primes for Resistance Against Powdery Mildew in Wheat - Twamley, Tony; Gaffney, Mark; Feechan, Angela (Frontiers in Plant Science, 2019)
Since many fungal pathogens develop resistance to fungicides, novel and low- cost alternative methods to improve plant health and fitness need to be developed. An approach to improve productivity in crops is to stimulate the plant’s own defence mechanisms via priming. Therefore, we investigated if a fermentation-based elicitor could prime plant defences against powdery mildew in wheat by inducing the expression of endogenous defence-related genes. Wheat seedlings were spray-treated with a fermentation-based elicitor eight days prior to inoculation with powdery mildew. Disease assays showed a significantly reduced number of powdery mildew pustules were formed on wheat treated with the mixed elicitor. In vitro sensitivity assays tested the ability of powdery mildew conidia to germinate on agar amended with the fermentation-based product and concluded that fungal germination and differentiation were also inhibited. Tissue samples were taken at time points pertaining to different developmental stages of powdery mildew infection. Significantly higher expression of PR genes (PR1, PR4, PR5 and PR9) were observed in the microbial fermentation mixture treated plants compared to untreated plants. These genes are often associated with the elicitation of plant defence responses to specific biotrophic pathogens, such as powdery mildew, suggesting an elicitor mediated response in the wheat plants tested. The product components were assessed, and the components were found to act synergistically in the microbial fermentation mixture. Therefore, this fermentation based elicitor provides an effective method for powdery mildew control.